HUBUNGAN PENGETAHUAN IBU PERSALINAN NORMAL DENGAN PEMBERIAN AIR SUSU IBU (ASI) DI IRINA D BLU RSUP PROF. dr. R. D. KANDOU MANADO - Runtunuwu, Mission T.; Sinolungan, J S.V.; Sambeka, Jolie (JURNAL KEPERAWATAN)
Abstrack: Knowledge is the result of â€œknowâ€, and this is happening after the person performs sensing against an object certain. Normal deliveryÂ  is the process of spending a conception can live results from the uterus through the vagina into the outside world. Granting breast-fed this presented in newborn infants until six months and continued until baby was two years old. The purpose of this research is to know the relation of maternal vaginal birth with knowledge of breast milk (BREAST MILK) of Irina D. Design this research is observation analytic with cross sectional.Â  The number of samples as many as 57 mother. The result data processed by the use of simple test correlation with the value of a correlation p<0,05 to hypothesis test. The result obtained such as 0,331 with the value of p<0.05 which means the presence of no relationship knowledge the mother normal delivery with the provision of breast-fed. So the higher knowledge mother childbirth normal the higher also mother give breast-fed at his son. To test the relationships between variables obtained the value of r is equal to zero there are 15, r equals the negative there are 25, r equals positive there are 20 also value interpretation 0.00-0,199 is 51, and 0.20-0,399 is 9. The result showed variable are associated with negative its interpretation very low. Advice to health workers to always ofÂ  providing a lot of information to mothers gave birth to importance of breast-fed for a baby. Keywords: Knowledge, Normal delivery, Granting breast-fed. Abstrak: Pengetahuan adalah hasil â€˜tahuâ€™, dan ini terjadi setelah orang melakukan penginderaan terhadap suatu objek tertentu. Persalinan adalah proses pengeluaran hasil konsepsi yang dapat hidup dari dalam uterus melalui vagina ke dunia luar. Pemberian ASI ini diberikan selama bayi baru lahir sampai 6 bulan dan dilanjutkan sampai bayi berusia 2 tahun. Tujuan penelitian ini untuk mengetahui hubungan pengetahuan ibu persalinan normal dengan pemberian air susu ibu (ASI) di Irina D. Desain penelitian ini adalah observasi analitik dengan cross sectional. Jumlah sampel sebanyak 57 ibu melahirkan. Hasil data yang diperoleh diolah dengan menggunakan uji korelasi sederhana dengan nilai korelasi p<0,05 untuk uji hipotesis. Hasil yang didapatkan yakni 0,331 dengan nilai p<0,05 yang berarti tidak adanya hubungan pengetahuan ibu persalinan normal dengan pemberian ASI. Jadi, pengetahuan ibu persalinan normal sangat tinggi maka banyak ibu yang memberikan ASI kepada anaknya. Untuk uji hubungan antar variabel didapatkan nilai r sama dengan nol ada 15, r sama dengan negatif ada 25, r sama dengan positif ada 20 juga nilai interpretasi 0,00-0,199 ada 51, dan 0,20-0,399 ada 9. Hasil menunjukan variabel yakni berhubungan negatif dengan interpretasinya sangat rendah. Saran kepada petugas kesehatan agar selalu memberikan informasi yang banyak kepada ibu-ibu melahirkan akan pentingnya pemberian ASI untuk bayi. Kata Kunci: Pengetahuan, Persalinan Normal, Pemberian ASI.